2018
DOI: 10.1155/2018/8412017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Low Glycaemic Index Sweeteners on Antioxidant, Sensory, Mechanical, and Physicochemical Properties of a Watermelon Jelly

Abstract: The replacement of sucrose by new noncariogenic and low glycaemic index sweeteners (isomaltulose and tagatose) and the addition of natural watermelon juice in jelly have been assessed in terms of composition, texture, colour, antioxidant activity, microbiology, and sensory properties. These analyses were performed initially and after 15 days of storage. Furthermore, the values were compared with those obtained in the analyses of a commercial watermelon jelly. The results showed that the antioxidant activity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
1
8
0
1
Order By: Relevance
“…The cupcake sweetened with tagatose was the least preferred by the evaluators, which coincides with a study conducted by Rubio-Arraez et al (2018), where the sensory acceptability of a commercial gelatin sample (with sugar), one with 50% isomaltulose and 50% tagatose and another with 100% tagatose was compared; the sample with total sugar substitution by tagatose was the worst evaluated [43]. Sample C3 in this study (sweetened with tagatose) was classified as cloying, with a bitter taste or with a strange taste; this is contradicted by a study carried out by Mogha et al (2016), in which they demonstrated that the sensory contribution of tagatose is beneficial, since it reduces the bitter aftertaste of the preparations significantly [44].…”
Section: Discussionsupporting
confidence: 86%
“…The cupcake sweetened with tagatose was the least preferred by the evaluators, which coincides with a study conducted by Rubio-Arraez et al (2018), where the sensory acceptability of a commercial gelatin sample (with sugar), one with 50% isomaltulose and 50% tagatose and another with 100% tagatose was compared; the sample with total sugar substitution by tagatose was the worst evaluated [43]. Sample C3 in this study (sweetened with tagatose) was classified as cloying, with a bitter taste or with a strange taste; this is contradicted by a study carried out by Mogha et al (2016), in which they demonstrated that the sensory contribution of tagatose is beneficial, since it reduces the bitter aftertaste of the preparations significantly [44].…”
Section: Discussionsupporting
confidence: 86%
“…In another study developed by Rubio‐Arraez et al. (2018), replacing sugar with different proportions of isomaltulose and tagatose was tested in the manufacture of watermelon jellies. According to the results, antioxidant activity increased with storage time in the control sample and the sample with isomaltulose and tagatose (50:50%).…”
Section: Resultsmentioning
confidence: 99%
“…With the results of this review, it can be observed that blends of different sweeteners are in general almost always favorable to the sensory aspects of sweet fruit preserves with partial or completely sugar reduction, with highlights for some positive outcomes using blends of natural sweeteners with artificial ones (Akesowan & Choonhahirun, 2014; Riedel et al., 2015; Santos et al., 2014; Souza et al., 2013), blends of artificial sweeteners (Lago‐Vanzela et al., 2011), or blends with natural bulk sweeteners (Farias et al., 2019; Lago‐Vanzela et al., 2011; Minh, 2020; Rubio‐Arraez, Capella, Castelló, et al., 2016; Rubio‐Arraez, Capella, Ortola, et al., 2016, Rubio‐Arraez et al., 2017; Rubio‐Arraez et al., 2018; Riedel et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dental diseases are the most prevalent noncommunicable sicknesses in the world and their treatment consumes between 5% and 10% of healthcare budgets in industrialized countries [4]. Additionally, simple sugars of rapid absorption cause glycemic peaks and the excess sugar can rapidly become fat in the body [8][9][10].…”
Section: Introductionmentioning
confidence: 99%